Continuing the Journey of Education, Training and Research (Journal of Training and Development, 2020)
The Journal of Training and Development has come up with issue 5, Volume 5 with the objectives of sharing the recent research findings in the field of Technical Vocational Education and Training (TVET) in research, training and development. This publication has a collection of valuable articles from TVET experts, scholars and educationalist. This training and development journals are considered to be valuable resources for the scholars, educationist and TVET experts and stakeholders. This issue consists of seven articles on different aspects of Training and Development.The article by Durga prasad Baral describe informal skills learning places in Nepal and tries to provides a typology that helps to understand the informal skills learning places and their formality. This paper analyses the existing legal frameworks and literature from domestic cultural practices adapting qualitative approach of inquiry. The paper concludes that the typology provides a sound conceptual basis for the identification of main categories and sub-categories of informal skills learning places in Nepal. The paper by Manoj Sharma Neuane scrutinizes the access and relevancy of presently available long term TVET programs and identify its gap with the market demand. The paper is the quantitative analysis of micro data is also adopted as a major basis and document review was also carried out while preparing the paper. The analysis shows that health-related programs are over-accessed while a clear gap is observed in the supply mechanism of TVET in the tourism and agricultural sectors. The paper revealed to promote agriculture and tourism sectors to promote TEVT programs both in quality and quantity in order to alleviate existing mismatch between demand and supply. The article by Kushmakar Bhatta highlight the positive effects that contributed by the Vocational Education and Training (VET) programs in socio-economic development of the disadvantaged and unemployed population of Nepal.   The primary data collected from   questionnaire and some field survey from the purposively sampled respondents- 405 VET graduates who after training are employed in their occupational sector. The study revealed that VET plays constructive role in employment and economic growth. However, it concludes with the recommendation that post training support to the participants is a must for functional VET and getting sustainable and decent employment in the labor market. survey for Vocational Education and Training (VET) graduates trained from different institutions purposively selected from the list of the VET graduates and interview questionnaires were sent to them. Apart from the questionnaire, some field survey was also administered for the qualitative data on role played by VET in employment, income and socio-economic development.    The article by Surya Prasad Newpane discuss the stories of women who uses their vocational skills to run a homestay in their community which is run by the Tharu and Bote of Nawalparasi. The qualitative approach was applied for carrying out this research and Amaltari homestay was selected as the research site. The stories of these women reveal that they have been using their skills in the area of hospitality, cooking traditional foods and crafting bamboo and wooden goods related skills  to serve guest. Despite of many barrier homestay contributed to the indigenous practice and supportive in enriching the Tharu and Bote women socially and culturally by using the vocational skills. The article by Narbikram Thapa assess the performance of private paravets in terms of quality of technical services. The qualitative and quantitative methods were adopted during field study where questionnaire survey, focus group discussion, direct field observation, force field analysis and score ranking was implemented. He concludes that the quality of the Private Paravets have found to be effective in terms of relevance, appropriateness, targeting, and sustainability issues. Project activities associated with Private Paravets promotion were observed appropriate in line with the needs and priorities of rural people of Nepal. Finally, the editorial team would like to express our heartfelt gratitude to all the authors who have contributed by providing their relevant and valuable creations. We would also like to express gratitude to the reviewers and TITI management team for their continuous support in publishing this journal. The team would also like to welcome articles from TVET experts, trainers and stakeholders in the field of training, development and research. We are also grateful to Tribhuvan University Central Library (TUCL) for providing their professionals support and encouragement to publish this journal online. Last but not least, we are thankful to the publisher for the publication of the print version of this journal.